In vitro micropropagation of Stevia rebaudiana Bertoni in Malaysia - Razak,Ummi Nur Ain Abdul (2014)
Stevia rebaudiana Bertoni is a medicinal plants and commercially use as non-caloric sweetener for diabetic patient. In the present study, a protocol was developed for in vitro micropropagation using 6-benzylamino purine (BAP) and Kinetin (Kn) for the formation of multiple shoot proliferation and Indole-3-acetic acid (IAA), Indole-3-butyric acid (IBA) and 1-Naphthaleneacetic acid (NAA) for the induction of roots. Maximum shoot formation (7.82 ± 0.7 shoots per explants) was observed on a Murashige and Skoog (MS) medium supplemented with 0.5 mg L-1 BAP and 0.25 mg L-1 Kn. The maximum number of roots (30.12 ± 2.1 roots per explants) was obtained on a MS medium containing 1.0 mg L-1 IBA. The well rooted plantlets were successfully weaned and acclimatized in plant soil with survival rate of 83.3 %.